Analisis Semiotika John Fiske dalam Film Just Mom - Yana Priana; Irwanto; Panji Suratriadi (CV Edujavare Publishing, 2025)
This family genre film tells the story of the old age of a mother named Siti (Christine Hakim), who feels lonely, because her children are busy with their own affairs. Plus, Siti's body was weakening because she was suffering from cancer. In the midst of longing for her children, Siti takes care of a homeless person named Murni (Ayu Shita) who suffers from ODGJ and is heavily pregnant. His presence made Siti's days more colorful. The film Just Mom shows that work born from the heart will be conveyed to the heart by the unrequited love a mother has for her children. And from humanizing a mother comes her love and affection throughout the masses. Using qualitative methods, this research involves observing films to identify the soul of a mother in her love for humans, both for her children and the people she cares about. This research is very, very important in upholding a mother's love which is not reciprocated by money, in fact mother's love conquers everything and cannot be replaced if mother's love in humanizing humans if one day is gone.